Digital Literacy Level of Civil Servants on Employee Applications in Sidoarjo Regency - Astrialita, Putri; Azizatun Nafi’ah, Binti (Jurnal Administrasi Publik dan Pemerintahan, 2025)
Digitalization has become a primary means of keeping up with the rapid advancements in technology. In the process of public service delivery, the use of digitalization can enhance public participation, accelerate development, and support community empowerment through information technology. This encourages civil servants (ASN) to master technology so that the provision of public services to the community can be optimal and excellent. This study aims to determine the level of digital literacy by measuring the digital literacy level of civil servants in Sidoarjo Regency in using Employee Management Applications. In this research, the author will measure the digital literacy level of 99 civil servant respondents, calculated using the Slovin formula with a margin of error of 10%. The study employs four measurement indicators from the Ministry of Communication and Information (Kominfo): digital skills, digital culture, digital ethics, and digital safety. A total of 33 statements will be presented in a questionnaire format. Before distributing these statements, the author has tested their validity and reliability. The results of the study indicate that the digital literacy level of civil servants in Sidoarjo Regency is 82%, which categorizes their digital literacy level as very high.